Activity patterns in seven captive lemur species: Evidence of cathemerality in Varecia and Lemur catta?. Issue 6 (3rd March 2017) - Bray, Joel; Samson, David R.; Nunn, Charles L.
Abstract : Cathemerality, or activity throughout the 24‐hr cycle, is rare in primates yet relatively common among lemurs. However, the diverse ecological conditions under which cathemerality is expressed complicates attempts to identify species‐typical behavior. For example, Lemur catta and Varecia have historically been described as diurnal, yet recent studies suggest that they might exhibit cathemeral behavior under some conditions. To investigate this variation, we monitored activity patterns among lemurs that are exposed to similar captive environments. Using MotionWatch 8 ® actigraphy data loggers, we studied 88 lemurs across seven species at the Duke Lemur Center (DLC). Six species were members of the family Lemuridae ( Eulemur coronatus, E. flavifrons, E. mongoz, L. catta, V. rubra, V. variegata ), while a seventh was strictly diurnal and included as an out‐group ( Propithecus coquereli ). For each 24‐hr cycle ( N = 503), we generated two estimates of cathemerality: mean night (MN) activity and day/night (DN) activity ratio (day and night cutoffs were based on astronomical twilights). As expected, P. coquereli engaged in the least amount of nocturnal activity according to both measures; their activity was also outside the 95% confidence intervals of all three cathemeral Eulemur species, which exhibited the greatest evidence of cathemerality. By these estimates, Varecia activity was most similar to Eulemur and exhibited substantial deviations from P. coquereli (β (MN) = 0.22 ± SE 0.12; β (DN) = −0.21 ± SE 0.12). L. catta activity patterns also deviated from P. coquereli (β (MN) = 0.12 ± SE 0.11; β (DN) = −0.15 ± SE 0.12) but to a lesser degree than either Varecia or Eulemur . Overall, L. catta displayed an intermediate activity pattern between Eulemur and P. coquereli, which is somewhat consistent with wild studies. Regarding Varecia, although additional observations in more diverse wild habitats are needed, our findings support the existence of cathemeral behavior in this genus.